First home or first away? Optimal ordering in two-legged ties - Peter-J. Jost (Managerial and Decision Economics, 2023)
We model a two-legged tie between two teams as a two-stage contest where each team chooses its attacking and defending effort for each leg. Assuming that each team has a home advantage for one of the matches, we analyze teams' preferences of order of play under different tiebreaking rules. We show that the answer depends on the size of the home advantage, the relative strengths of both teams, and the tiebreaking rule. In particular, we identify under which conditions a team prefers to play first home or first away and under which conditions they are indifferent.
Keywords: 650